2016
DOI: 10.15171/ijhpm.2016.135
|View full text |Cite
|
Sign up to set email alerts
|

The Life Story Experience of "Migrant Dentists" in Australia: Potential Implications for Health Workforce Governance and International Cooperation

Abstract: Background: The migration of dentists is a major policy challenge facing both developing and developed countries. Dentists from over 120 countries migrate to Australia, and a large proportion are from developing countries. The aim of the study was to assess the life story experience (LSE) of migrant dentists in Australia, in order to address key policy challenges facing dentist migration. Methods: A national survey of all migrant dentists resident in Australia was conducted in 2013. Migrant experiences were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…Contrary to findings from previous research on country of qualifications, 36,37 and level of education and specialization, 39 there was no significant association between these professional factors and stress in this study. Other research in New Zealand showed that overseas-qualified dentists felt more isolated than domestically trained dentists, and attributed this to the public's negative reactions to overseas-trained clinicians.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to findings from previous research on country of qualifications, 36,37 and level of education and specialization, 39 there was no significant association between these professional factors and stress in this study. Other research in New Zealand showed that overseas-qualified dentists felt more isolated than domestically trained dentists, and attributed this to the public's negative reactions to overseas-trained clinicians.…”
Section: Discussioncontrasting
confidence: 99%
“…However, older migrant dentists have previously been shown to have higher levels of job satisfaction than younger migrant dentists. 38 Dentists without postgraduate qualifications and without a speciality have poorer well-being than their counterparts. 39 A teaching role might contribute to poor well-being, 39 although Rutter et al 40 reported that teaching might mitigate stress because of lessened isolation, increased self-esteem and autonomy and added interest in patients as a source of teaching opportunities.…”
Section: Australian Dental Journalmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Prior research has suggested a tendency to ‘time-based’ mobility patterns, with migrant dentists changing to work more in the public sector or rural and remote or disadvantaged areas in their initial stage of migration to Australia, but gradually preferring to work in the private sector or in major cities as they become more familiar with Australian life. 10 …”
Section: Introductionmentioning
confidence: 99%